Penilaian Mutu Pendidikan Berdasarkan Ketersediaan Sarana Prasarana di Masa Pandemi Covid-19 Menggunakan Metode AHP - Gilbert Yesaya Likumahua; Sri Yulianto Joko Prasetyo (STMIK Budi Darma, 2022)
This study aims to know the infrastructures used for the teaching-learning process and the effort made to improve education quality during the pandemic of Covid-19. The method used by the researcher was descriptive qualitative. The subjects of this study were four senior high schools in Salatiga. AHP method approach was used in conducting this study. Meanwhile, Questionnaires and interviews were used as instruments for data retrieval. The data collected will be analyzed using literature-based data triangulation techniques. The results showed that some criteria have a high impact on improving the quality of education based on infrastructure tools: bandwidth with 0,397 (39%), lcd with 0,245 (24%), computer lab with 0,242 (24%), the number of computers 0,064 (6%), and the last was the access point with 0.053 (5%).